PEDAGOGICAL CONDITIONS OF EFFECTIVE FORMATION OF SPIRITUALITY SENIOR STUDENTS IN PROCESS INTERPRETATIONS OF WORKS - L.V. Butenko (Academy of Cognitive and Natural Sciences, 2022)
The article is devoted to the questions of forming spirituality of senior pupils by means of interprétation of artistic literature, especially pedagogical conditions, which will contrihute effective performing of described influence.